The Politeness Strategy Reflected in English Class of Senior High School: Case Study - Ayu Triwidiastuti (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The global outbreak of the COVID-19 Pandemic has spread worldwide, affecting almost all countries and territories. Lockdown and staying home strategies have been put in place as the needed action to flatten the curve and control the transmission of the disease (Sintema, 2020). Several schools and colleges and universities have discontinued face-to-face teaching. Furthermore, and alternative educational method, the digital learning was invented (Dhawan, 2020). This research was conducted to analyze the politeness strategy used by Teacher and students on Online English Learning Process. She describes what types of politeness strategies used by English Teacher and Students on Online Teaching Learning Process and what the most dominant type of politeness strategy used by Teacher Students on English Online Teaching Learning Process. The research was conducted in August until October 2021 in zoom meeting in SMAN 1 Rogojampi, Banyuwangi. This research was descriptive qualitative research. The subject of this research was an English teacher and students of SMAN 1 Rogojampi, Banyuwangi. She used descriptive qualitative research, and plenty of steps to analyze the data, namely; data reduction, data display, and conclusion drawing. The data validation technique used is methodological triangulation. She used Brown and Levinson‟s Politeness strategies theory, namely; bald on record, positive politeness, negative politeness strategy, off record, and say nothing. Bald on record is used by the speaker if there is unambiguously intention (Brown and Levinson, 1987: 95). In bald on record, the speaker does not need to do FTA. Instead, the speaker speaks more directly under some considerations like in an urgent situation. Then, positive politeness mostly used in a group of friends or those who know each other well. It is also trying to minimize the distance between the speaker and the hearer. Meanwhile, apologize will be found in negative politeness to avoid the hearer feels offence by showing respect. Next, Off-Record is also called as indirect viii politeness strategy. It is used by the speaker when the unambiguously intention is more than one. There are also some linguistic realizations that may include such as metaphor and irony, rhetorical questions, understatement, tautologies, all kinds of hints that the speaker wants or means to state and non-direct sentence so that the meaning seems negotiable (Brown and Levinson, 1987: 71). The result showed that, English teacher used all of the four Brown and Levinson‟s politeness strategies, namely bald on record strategy, positive politeness strategy, negative politeness strategy, off record strategy. The students used all the three Brown and Levinson‟s politeness strategies, namely bald on record, positive politeness strategy, negative politeness strategy. The use of politeness strategy of students was dominated by positive politeness strategy.
Reuploud file repositori 22 Jan 2026_Firli
Keywords: Sosiokultura; Pragmatik; The Politeness Strategy